The Moderating Effect of Government Ownership on the Relationship between Cash Flow and Firm’s Performance for Construction Industry in Malaysia - Nazaria, Md. Aris; Nurhidayah, Sokat; Salawati, Sahari (HRMARS, 2020)
This study attempts to measure the circumference of the cash utilization activities from operations activity, investment activity, and financing activity towards firms’ performance of the construction industry in Malaysia by using Government Ownership as the moderating variable. This study essentially using a secondary data that obtain from the annual report for the year 2014 to 2018. The data of the cash flow variable and firms’ performance was originally keep recorded in a monetary value whilst data for Government Ownership was obtained through a content analysis. The findings revealed that there is negative relationship with Net Cash Flow towards the Return on Assets. The results demonstrated that the Net Cash Flow in Operating activity is the most influenced by Government Ownership. The Net Cash Flow in Investing activity is significantly affected, while the Net Cash Flow in Financing is the least affected by Government Ownership. In other words, although the government has an authority to influence the economic activity in the market, the government interferein their capital structure does not effectively affect the firms’ performance of construction sector in Malaysia.